Diagnóstico da infecção cervical pelo HPV: avaliação colposcópica, citopatológica e histopatológica - Linhares, Liliane Ribeiro (Brazilian Journal of Sexually Transmitted Diseases, 1994)
This study contains a bibliografíc review about certai n features of human papillomavirus (HPV), its biology, kinds of clinicai infection, management, prognostíc and its possible relationship with genital carcinogenesis with especial emphasis 011 diagnosis colposcopic, cytologic and histologic. We studied 52 patietns, at Ambulatório Preventivo do Instituto de Ginecologia da Universidade Federal do Rio de Janeiro, from march 1989 to january 1990, with colposcopic suspection ofhuman papillomavirus infection. The patients were submitted to Papanicolau smear and directed cervical biopsy. ln this group the result ,,vas that the majority (98,1%) of cervical HPV infections was subclinical at colposcopy. The flat condyloma was the most frequent feature seen (96.2%). ln 27 patients (52%) we found histologic and colposcopic correlation and in 8 ( 15.4%), cytological and colposcopic correlation, were seen. Taken that histologic seens to be a more precise diagnosis. We drew a conc:lusion that colposcopic isn't good with unique diagnosis method.